Between symbolism and metaphor - Gecas, Saulius (Journal of Architecture and Urbanism, 2014)
The article provides a discussion of symbolic aspects and uses of metaphors in Massimiliano Fuksas architecture. Despite of the fact that his architectural projects are very different they are sculptural and abstract leading to ambiguous reflections. The author argues that each architectural project of Massimiliano Fuksas can be related to certain metaphors and level of symbolisation. His metaphors are often metaphors for our feelings, they are emotionally understandable and yet not so easy to name. The article is an attempt to expose and analyze them.